It is currently 17 Nov 2017, 10:40

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

If x + y = 6 and 3x – y = 4, then x – y is equal to

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Expert Post
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 42250

Kudos [?]: 132495 [0], given: 12323

If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 24 Oct 2017, 01:49
00:00
A
B
C
D
E

Difficulty:

  15% (low)

Question Stats:

87% (00:56) correct 13% (00:29) wrong based on 63 sessions

HideShow timer Statistics

Kudos [?]: 132495 [0], given: 12323

Intern
Intern
avatar
B
Joined: 20 Aug 2016
Posts: 23

Kudos [?]: 6 [0], given: 93

GMAT 1: 570 Q46 V23
WE: Information Technology (Other)
Reviews Badge
Re: If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 24 Oct 2017, 02:32
solving the eq we get x=5/2 and y=7/2
implies
x-y = -2/2 = -1

Thanks.

Kudos [?]: 6 [0], given: 93

Intern
Intern
avatar
B
Joined: 16 Feb 2017
Posts: 7

Kudos [?]: 0 [0], given: 11

Concentration: General Management, Social Entrepreneurship
CAT Tests
Re: If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 24 Oct 2017, 20:03
On solving this equation, we get x=2.5 and y=3.5 . Hence, (x-y)= -1. Ans-A

Kudos [?]: 0 [0], given: 11

Expert Post
Target Test Prep Representative
User avatar
S
Status: Head GMAT Instructor
Affiliations: Target Test Prep
Joined: 04 Mar 2011
Posts: 1684

Kudos [?]: 900 [0], given: 5

Re: If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 26 Oct 2017, 15:50
Bunuel wrote:
If x + y = 6 and 3x – y = 4, then x – y is equal to

(A) –1
(B) 0
(C) 2
(D) 4
(E) 6


Since x + y = 6, then x = 6 - y. Substituting this into the second equation for x, we have:

3(6 - y) - y = 4

18 - 3y - y = 4

-4y = -14

y = 3.5

Thus, x = 6 - 3.5 = 2.5 and x - y = 2.5 - 3.5 = -1.

Answer: A
_________________

Jeffery Miller
Head of GMAT Instruction

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

Kudos [?]: 900 [0], given: 5

Director
Director
avatar
P
Joined: 22 May 2016
Posts: 968

Kudos [?]: 335 [0], given: 587

If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 27 Oct 2017, 12:05
Bunuel wrote:
If x + y = 6 and 3x – y = 4, then x – y is equal to

(A) –1
(B) 0
(C) 2
(D) 4
(E) 6

Add:
\(x + y = 6\)
\(3x-y = 4\)
-----------------------
\(4x = 10\)
\(x =\frac{10}{4}=\frac{5}{2}\)

\(x + y = 6\)
\(\frac{5}{2} + y = \frac{12}{2}\)
\(y = (\frac{12}{2}-\frac{5}{2}) = \frac{7}{2}\)

\((x - y)\)
\((\frac{5}{2}-\frac{7}{2})= -\frac{2}{2}= -1\)

Answer A

Kudos [?]: 335 [0], given: 587

Intern
Intern
User avatar
S
Joined: 02 Sep 2015
Posts: 37

Kudos [?]: 27 [0], given: 21

Location: India
Concentration: General Management, Entrepreneurship
Schools: Sauder 'Dec 18
GPA: 3.79
WE: General Management (Energy and Utilities)
GMAT ToolKit User
Re: If x + y = 6 and 3x – y = 4, then x – y is equal to [#permalink]

Show Tags

New post 28 Oct 2017, 04:45
x +y =6 ... Eq (1)
3x-y =4 ... Eq (2)

Adding Eq (1) & (2)
we get 4x=10
hence 2x =5

Eq (2) : 3x-y =4
Hence, x-y = 4-2x = 4-5= -1. Answer = A.

Kudos [?]: 27 [0], given: 21

Re: If x + y = 6 and 3x – y = 4, then x – y is equal to   [#permalink] 28 Oct 2017, 04:45
Display posts from previous: Sort by

If x + y = 6 and 3x – y = 4, then x – y is equal to

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.